2020
DOI: 10.1109/tns.2020.3021612
|View full text |Cite
|
Sign up to set email alerts
|

Hybrid Multipixel Array X-Ray Detectors for Real-Time Direct Detection of Hard X-Rays

Abstract: X-ray detectors currently employed in dosimetry suffer from a number of drawbacks including the inability to conform to curved surfaces and being limited to smaller dimensions due to available crystal sizes. In this study, a hybrid X-ray detector (HXD) has been developed which offers real-time response with added advantages of being highly sensitive over a broad energy range, mechanically flexible, relatively inexpensive and able to be fabricated over large areas on the desired surface. The detector comprises … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 44 publications
0
8
0
Order By: Relevance
“…[142][143][144] Retaining flexibility with increasing PVK thickness is a challenge, and a PVK in a porous nylon membrane, developed for flexible direct X-ray detection, demonstrated 2/3 mm minimum bending radii in 130/240 μm thick devices, respectively. However, unlike direct detectors and solar cells, which require charge transport considerations and compatible transport layers and contacts 145 , scintillators are much simpler, making the prospect of developing a flexible scintillator promising. Alternate uses of flexibility could include accurately measuring dose delivery with detectors conforming to body parts.…”
Section: Low Temperature Fabrication and Flexible Detectionmentioning
confidence: 99%
“…[142][143][144] Retaining flexibility with increasing PVK thickness is a challenge, and a PVK in a porous nylon membrane, developed for flexible direct X-ray detection, demonstrated 2/3 mm minimum bending radii in 130/240 μm thick devices, respectively. However, unlike direct detectors and solar cells, which require charge transport considerations and compatible transport layers and contacts 145 , scintillators are much simpler, making the prospect of developing a flexible scintillator promising. Alternate uses of flexibility could include accurately measuring dose delivery with detectors conforming to body parts.…”
Section: Low Temperature Fabrication and Flexible Detectionmentioning
confidence: 99%
“…[ 12 ] Preliminary studies [ 12 ] for this system demonstrated its suitability as a flexible detector where detectors were deformed to a reasonable radius of curvature of ≈ 3 mm with recent developments indicating its use as a conformable detector for dose mapping in radiotherapy. [ 13 ] However, in both of the above reports, the detectors suffered from high dark currents that are 3 – 4 orders of magnitude higher than state‐of‐the‐art detector technologies. [ 12,13 ] Recently, we reported [ 14 ] a methodology to achieve ultra‐low dark currents that are well below the industrial requirements of 10 pA mm −2 , in combination with exceptionally high sensitivities under clinical 6 MV hard X‐ray radiation conditions.…”
Section: Introductionmentioning
confidence: 99%
“…[ 13 ] However, in both of the above reports, the detectors suffered from high dark currents that are 3 – 4 orders of magnitude higher than state‐of‐the‐art detector technologies. [ 12,13 ] Recently, we reported [ 14 ] a methodology to achieve ultra‐low dark currents that are well below the industrial requirements of 10 pA mm −2 , in combination with exceptionally high sensitivities under clinical 6 MV hard X‐ray radiation conditions. These detectors also demonstrated significant improvements in X‐ray response parameters such as fast response times and low beam angle dependence owing to the unique structuring of the film morphology.…”
Section: Introductionmentioning
confidence: 99%
“…We achieved sensitivity to X-rays up to (4.10 ± 0.05) 10 10 µC Gy -1 cm -3 , which represents not only the highest value reported so far for a fully-organic tissue equivalent , with those reported at the state of the art for thin-film detectors based on perovskite (red triangles), organic-hybrid (blue circles), and full-organic (black squares) active layers. [1,[4][5][6][7][8][9][10][12][13][14][50][51][52][53][54][55][56][57][58][59][60][61] active layer, but it is also higher than most perovskite filmbased X-ray detectors, as shown in Figure 5b. Considering that our active layer is composed of very thin films (i.e., a few tens of nanometers), we also plotted the corresponding graph of the sensitivity values per unit area in Figure S8 (Supporting Information).…”
Section: Resultsmentioning
confidence: 98%
“…b) Comparison of the sensitivity values per unit volume achieved in this work (green triangle), with those reported at the state of the art for thin‐film detectors based on perovskite (red triangles), organic‐hybrid (blue circles), and full‐organic (black squares) active layers. [ 1,4–10,12–14,50–61 ] c) Layout and POM images of the 4 pixels array BAMS printed TMTES:PS detector. d) OFET transfer characteristics of the 4 pixels of the array.…”
Section: Resultsmentioning
confidence: 99%